Meta Analysis the Effect of Electronic Health-based Self Management in Controlling Blood Pressure in Hipertensive Patients - Rahmah, Aulia Siti Nur; Tamtomo, Didik; Murti, Bhisma (Journal of Health Policy and Management, 2023)
Background Consistent application of self-management is important in efforts to improve the quality of life and health status of hypertensive patients. Electronic health is here to facilitate self-management of hypertensive patients and provide health information to health workers in real time and promote lifestyle modifications. The purpose of this study was to analyze the influence of electronic health-based self-management on blood pressure control in hypertensive patients.Subjects and Method: : This study is a meta-analysis using PICO namely Population: Hypertensive patients; Intervention: Self-management based on electronic health; Comparison: No self-management based on electronic health; Outcome: Systolic and diastolic blood pressure. This study uses articles from several databases, i.e Pubmed, Google Scholar, Science Direct and the Cochrane Library using the following keywords “Hypertension” OR “Hypertensive” OR “Blood Pressure” OR “High Blood Pressure” AND “Self Management” OR “Self Care” OR “Self Monitoring” AND “Electronic Health” OR “eHealth” OR “Telemedicine” OR “Telehealth” OR “mHealth” OR “Mobile Health” OR “Mobile Application” OR “Message Text” OR “Phone Calls”. Articles included in the research are articles that use English with an RCT study design whose publication is within the period of 2012-2022. The steps in the systematic review are carried out based on the PRISMA flow diagram guidelines. Quantitative analysis was carried out using Review Manager (Revman) 5.3.Results: There were 9 articles from South Africa, America, South Korea, Spanish, England, Scotland, and Honduras, with a sample size of 3,071 hypertensive patients concluded that electronic health-based self-management could reduce systolic blood pressure by 0.38 units and was statistically significant (SMD= -0.38; 95% CI = -0.55 to -0.20; p<0.001 ). The meta-analysis synthesized 9 studies with a total sample size = 2.095 hypertensive patients concluded that electronic health-based self-management could reduce diastolic blood pressure by 0.21 units and was statistically significant (SMD= -0.21; 95% CI = -0.29 to -0.12; p< 0.001).Conclusion: Electronic health-based self-management can reduce systolic and diastolic blood pressure control in hypertensive patients.Keywords: Self management, electronic health, blood pressure, hypertensionCorrespondence:Aulia Siti Nur Rahmah. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: rahmaaulia500@gmail.com. Mobile: 08156865373.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.04